تقدير الأبعاد الأساسية لسفن البضائع العامة الجديدة في مرحلة التصميم الأولي - أحمد غالب (Latakia University Journal -Engineering Sciences Series, 2019)
Determination the principal dimensions of new ships forms a very important Phase in overall ship design. These dimensions decide many of the ship’s characteristics, e.g. stability, dead weight, spatial of holds, power requirements, and even economic efficiency. The desired characteristics can usually be achieved with various combinations of dimensions. This choice allows an economic optimum to be obtained whilst meeting company requirements. There are many available formulae determine the principal dimensions of ship, from similar ships or from formulae and diagrams ,derived from a data base of similar ships. The aim of this paper is to introduce formulae that can be used to quickly predict the main dimensions in preliminary design stage. These formulae depend on statistical data of exiting ships. The obtained results were compared with results of existing formulae, it was found that the obtained results are closer to the dimensions of existing ships. يشكل تحديد الأبعاد الأساسية للسفن مرحلة هامة في التصميم الكلي للسفينة. تحدد هذه الأبعاد العديد من الخصائص للسفينة، كالاتزان، فراغات الحمولة، متطلبات الطاقة، والفعالية الاقتصادية للسفينة. يمكن أن تنجز الخواص التقنية للسفينة بأبعاد مختلفة بشكل كبير، يكمن الاجراء الأمثل في تحديد هذه الأبعاد طبقا لمعايير موصوفة تساهم في تقليل تكاليف الانتاج ومتطلبات الطاقة. هناك العديد من الطرق المتاحة التي تعتمد في تحديد الأبعاد الأساسية للسفينة على سفن مشابهة، أو بالاعتماد على صيغ ومخططات مشتقة من بيانات لسفن مشابهة. لكن بعض هذه الصيغ غير مناسبة لتصميم السفن الحديثة. تمّ في هذا البحث تقديم صيغ تستخدم في حساب الابعاد الأساسية بسرعة في مراحل التصميم الأولي للسفينة. تعتمد هذه الصيغ على البيانات الاحصائية لسفن موجودة. تمّ مقارنة النتائج التي تم الحصول عليها من الصيغ المقترحة مع نتائج الصيغ الموجودة، وقد تبين بأنها تعطي أبعاد قريبة من أبعاد السفن الموجودة في الاستخدام.